Dispute Resolution Model in Sewangi Island Village Communities Based on Wetlands - Erliyani, Rahmida; Syahrida, Syahrida; Rahmawati, Diana; Sihite, Dermawatie; Farah, Gusti Alya Fathia; Amalia, Berliany; Geovandry, Dimas (Universitas Syiah Kuala, 2024)
Based on Law Number 3 of 2024, an amendment to Law Number 6 of 2014 concerning Villages, it regulates the concept of a village as a legal community unit with certain territorial boundaries with the authority to regulate and manage its own government affairs. In carrying out village government led by the village head, one of the village head's obligations according to the law is to resolve disputes in the village community, this is stated in the provisions of article 26 of the law. This is interesting to research in socio-legal legal studies, especially in studies regarding dispute resolution models or village community disputes. These legal problems were analyzed based on empirical legal research methods by exploring field data based on interview techniques at the research location in Sewangi Island Village, Batola Regency, South Kalimantan Province.The research results show that the existence of a village head is very important in resolving disputes or disputes in village communities whose cultural characteristics are generally wetland-based, namely as communities on the banks of the Barito river, with a communal and traditional community culture. According to legal studies, the dominant form of dispute resolution is the non-litigation form of resolution. The dispute resolution model applied is a deliberative dispute resolution model which leads to a dispute resolution model towards Mediation and Conciliation, as well as directed coordination with law enforcement if it is resolved towards a Litigation process.